2019
DOI: 10.1113/jp276807
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles and molecular mechanisms of K+‐Cl cotransport in the mammalian kidney and cardiovascular system: where are we?

Abstract: In the early 80s, renal microperfusion studies led to the identification of a basolateral K+‐Cl− cotransport mechanism in the proximal tubule, thick ascending limb of Henle and collecting duct. More than ten years later, this mechanism was found to be accounted for by three different K+‐Cl− cotransporters (KCC1, KCC3 and KCC4) that are differentially distributed along the renal epithelium. Two of these isoforms (KCC1 and KCC3) were also found to be expressed in arterial walls, the myocardium and a variety of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 112 publications
(355 reference statements)
0
11
0
Order By: Relevance
“…As it stands, nine CCCs have now been uncovered (Garneau et al, 2017; Garneau, Marcoux et al, 2019; Garneau, Slimani et al, 2019; Marcoux et al, 2017). As shown in Figure 1b, they fall into four phylogenetic clades.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…As it stands, nine CCCs have now been uncovered (Garneau et al, 2017; Garneau, Marcoux et al, 2019; Garneau, Slimani et al, 2019; Marcoux et al, 2017). As shown in Figure 1b, they fall into four phylogenetic clades.…”
Section: Main Textmentioning
confidence: 99%
“…However, their transport dependence on extracellular [Na + ], [K + ], and [Cl − ] was studied by different research groups and found to be consistent with a one ion‐binding site model for each cation and a two ion‐binding site model for Cl − (Gagnon et al, 2004; Gagnon, Forbush, Caron, & Isenring, 2003; Gimenez & Forbush, 2007; Gimenez, Isenring, & Forbush, 2002). It should be nonetheless remembered that such models were inferred from Hill coefficients and that they thus only provide an estimate of the minimal number of binding sites involved (Garneau et al, 2017; Garneau, Marcoux et al, 2019; Garneau, Slimani et al, 2019; Marcoux et al, 2017).…”
Section: Main Textmentioning
confidence: 99%
“…1): KCC1 belongs to one branch along with the three other KCC, the Na + -dependent CCC belong to another branch and the remaining two CCC (called CCC8 and CCC9) belong to each an independent branch. Overall, KCC1 shares higher identity with KCC3 (~ 75%) than with any of the other CCC [1, 3].…”
Section: Main Textmentioning
confidence: 99%
“…K + -Cl − cotransporter 1 (KCC1) is a membrane protein that mediates the symport of K + and Cl − ions through the surface of most animal cells [1]. It is also referred to as SLC12A4 based on the Human Genome Organization (HUGO) nomenclature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation